Spontaneous polarization in the cluster ferroelectric system close to the phase transition point - Korynevskii, N.A. (Condensed Matter Physics, 1999)
A two-stage layer by layer integration of the ferroelectric two-particle cluster system partition function functional is made in the quartic basic distribution of the dipole momentum ﬂuctuation approximation. The shape of the layers of integration is determined by peculiarities of ﬂuctuation processes (of the Gaussian and the non-Gaussian types) for separate subsets of collective variables. The minimization procedure of the partition function functional unintegrated over one variable (with quasimomentum and Matsubara's frequency equal to zero) gives an equation for the order parameter (i.e., the spontaneous polarization) of the system. Solutions of this equation at various values of system parameters and external ﬁeld are found in the Tc neighbourhood.